Legal Protection Against Franchise Business In Maintaining Product Quality (Case study of Fremilt Pasar Kliwon Surakarta branch) - Risma Dewi Hermawan; Aris Prio Agus Santoso; Rina Arum Prastyanti (Universitas PGRI Madiun, 2021)
The government needs to develop a franchise business in order to expand job opportunities, for that the government creates efforts to protect franchisees and franchisors so that the government issues government regulation no. 42 of 2007 concerning franchise business (Franchise). However, the reality is that there are still many franchises that do not fulfill their obligations to franchisors, such as some franchises that do not carry out SOPs (Standard Operating Procedures) with initial provisions. The problems raised in this study are about how the legal protection for the parties concerned in the franchise agreement, namely the franchisor and the franchisee and the forms of rights and obligations between the franchisor and the Fremilt product franchise, Pasar Kliwon Surakarta branch. This type of research uses empirical research, namely individual research related to social life, in this study the researcher tries to uncover legal protection for franchisees and franchisors of Fremilt products, Pasar Kliwon Surakarta branch. This research is taken from many facts in society. Based on the research, it was found that there is legal protection for franchisees and franchisors so that the taste of the product will be maintained its authenticity and between the two parties can run the SOP in accordance with the provisions of the agreement at the beginning. In addition, the franchisee and the franchisor will feel protected and will get a guarantee of certainty if something goes wrong that harms both parties